Pre-hospital transport times and survival for Hypotensive patients with penetrating thoracic trauma - Swaroop, Mamta (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Achieving definitive care within the “Golden Hour” by minimizing response times is a consistent goal of regional trauma systems. This study hypothesizes that in urban Level I Trauma Centers, shorter pre-hospital times would predict outcomes in penetrating thoracic injuries. MATERIALS AND METHODS: A retrospective cohort study was performed using a statewide trauma registry for the years 1999-2003. Total pre-hospital times were measured for urban victims of penetrating thoracic trauma. Crude and adjusted mortality rates were compared by pre-hospital time using STATA statistical software. RESULTS: During the study period, 908 patients presented to the hospital after penetrating thoracic trauma, with 79% surviving. Patients with higher injury severity scores (ISS) were transported more quickly. Injury severity scores (ISS) ≥16 and emergency department (ED) hypotension (systolic blood pressure, SBP <90) strongly predicted mortality (P < 0.05 for each). In a logistic regression model including age, race, and ISS, longer transport times for hypotensive patients were associated with higher mortality rates (all P values <0.05). This was seen most significantly when comparing patient transport times 0-15 min and 46-60 min (P < 0.001). CONCLUSION: In victims of penetrating thoracic trauma, more severely injured patients arrive at urban trauma centers sooner. Mortality is strongly predicted by injury severity, although shorter pre-hospital times are associated with improved survival. These results suggest that careful planning to optimize transport time-encompassing hospital capacity and existing resources, traffic patterns, and trauma incident densities may be beneficial in areas with a high burden of penetrating trauma.